L’extravagance gasconne dans Le Gascon extravagant : un déguisement « pour parler librement de tout » - Jean-Pierre Cavaillé (Les Dossiers du GRIHL)
Gascon Extravagance in The Extravagant Gascon : a disguise « to talk freely about everything » : The article presents an analysis of the figure of the Gascon cavalier and of his extravagance in this « comic novel » by restituting it in relation to the preconceived ethnotype of the Gascon. It would appear, firstly, that this ethnotype is far from being purely negative and that it is not merely synonymous with bragging and bluster. Its positive connotations are, indeed, numerous and principally tied to the still venerated image of Henry of Navarre with his political and sabre-rattling aura, his reputation for intrepidness which went beyond the sole bounds of arms and which came to invest just as surely the field of language and culture. From this point of view, Clairville’s novel confirms the typical depiction of the Gascon, in the sense that it restitutes and exploits ambivalence and structural complexity, and only rejects the most monolithic and caricatural version thereof. This takes nothing away from the originality of the enterprise, which resides in the unabashed usage of the figure of the Gascon as a mask or disguise for tackling issues subject to strict censorship, most notably, the still burning question, in the aftermath of the Loudun Affair, of demoniac possession.